My life in a cat house : true tales of love, laughter, and living with five felines - Cooper, Gwen, 1971- (BenBella Books, Inc., 2018)
"This collection of eight purr-fect cat stories is filled with all the humor and heart Gwen's devoted readership has come to know and love" --